Daya Terima Formulasi Penambahan Sayur (Wortel, Bayam, dan Brokoli) pada Nugget Ayam (NUSA) - Fithroh Ariwibowo; Putri Ramadhani Ayuningtyas (Universitas Airlangga, 2023)
Background: The consumption of vegetables in Indonesian society, especially for school-age children, is relatively low. The 2013 Basic Health Research results show that 96.4% of the population aged 10 years consume less vegetables in West Java. One study stated that as many as 70.2% of children at SDN 139 Sukarasa Bandung consume less fruit and vegetables. There is a shift in consumption style which makes ready-to-cook and ready-to-eat food an alternative choice for people to serve to children (Sugiarto, et al. 2018). One example of a ready-to-cook food menu is nugget. The formulation of adding vegetables to nuggets can be an alternative to increase the acceptance of vegetables in school-age children. Objectives: Knowing the acceptability of the formulation of adding vegetables (carrots, spinach, and broccoli) to chicken nuggets (NUSA) Methods: The preliminary study was conducted on 5 limited panelists and the follow-up study was conducted on 25 Darul Muchsin ALMA'HAD Foundation students aged 10-12 years. Results: Untrained panelists identified the most preferred formula, namely formula three (F3). Based on the Kruskal Wallis statistical test, there was no significant difference in the addition of various types of vegetables to the characteristics of color, aroma, texture, and taste of the nugget formula (F0, F1, F2, and F3). The results of the Mann Whitney difference test on each characteristic of color, aroma, texture, and taste have a significance value of > 0.05, which means there is no specific difference of each characteristic of color, aroma, texture, and taste between formulas (F0-F1, F0-F2, F0-F3, F1-F2, F1-F3, and F2-F3). Conclusions: The addition of vegetables to NUSA nuggets had good acceptability, especially formula 3 and there was no significant difference between the addition formulas (F1, F2, and F3) and the standard formula (F0).